2022
DOI: 10.1038/s41536-022-00269-w
|View full text |Cite
|
Sign up to set email alerts
|

Injectable decellularized cartilage matrix hydrogel encapsulating urine-derived stem cells for immunomodulatory and cartilage defect regeneration

Abstract: Reconstruction of complex cartilage defects has remained a great challenge for tissue engineering due to the lack of stem cells and chronic inflammation within the joint. In this study, we have developed an injectable pig cartilage-derived decellularized extracellular matrix (dECM) hydrogels for the repair of cartilage defects, which has shown sound biocompatibility and immunomodulatory capacity both in vitro and in vivo. The dECM hydrogels can enhance the chondrogenic differentiation of human urine-derived st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…In addition, tissue engineering can be customized to the individual patient's needs because the cells used in the procedure are derived from the patient's tissue, reducing the risk of immune rejection. 34 However, tissue engineering is still in the early stages of development, and its clinical efficacy and safety need to be evaluated through preclinical and clinical studies. In addition, the manufacturing process of tissueengineered cartilage is complex and expensive, which may limit patient access.…”
Section: Osteochondral Autografting (Oats)mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, tissue engineering can be customized to the individual patient's needs because the cells used in the procedure are derived from the patient's tissue, reducing the risk of immune rejection. 34 However, tissue engineering is still in the early stages of development, and its clinical efficacy and safety need to be evaluated through preclinical and clinical studies. In addition, the manufacturing process of tissueengineered cartilage is complex and expensive, which may limit patient access.…”
Section: Osteochondral Autografting (Oats)mentioning
confidence: 99%
“…The cells are cultured in a controlled environment, and growth factors are added to promote their differentiation and the production of new cartilage tissue. Tissue engineering has the potential to provide a durable, functional repair of cartilage defects because the newly generated cartilage tissue can fuse with surrounding tissue and provide an available replacement for damaged cartilage. In addition, tissue engineering can be customized to the individual patient’s needs because the cells used in the procedure are derived from the patient’s tissue, reducing the risk of immune rejection . However, tissue engineering is still in the early stages of development, and its clinical efficacy and safety need to be evaluated through preclinical and clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Zeng et al reported a pig cartilage-derived decellularized extracellular matrix with stem cell encapsulation for repairing cartilage defects through lyophilization and enzyme digestion treatments. 79 Based on similar procedures, Neves et al reproduced the renal microenvironment in vitro by separating the decellularized extracellular matrix from porcine kidneys. 80 In recent years, researchers are exploring commercialization possibility of decellularized extracellular matrix but still faced with the challenges of biosafety, availability, effective organ integration, batch-to-batch variability, etc.…”
Section: Natural Biomaterialsmentioning
confidence: 99%
“…Recent advances have brought about the springing up of biomaterials with desired morphology from diverse fabrication techniques ranging from microfluidics, 79,[99][100][101] self-assembly, 102 microfabrication 103 to 3D printing, [75][76][77]80,104 etc. 105,106 In fact, human organs have evolved with delicate and diverse microstructures, for example, globular structure of pulmonary alveoli, fibrous structure of muscles, and membrane structure of skin.…”
Section: Basic Design Of Biomaterialsmentioning
confidence: 99%
“…In the effect of developing in situ forming hydrogels for repairing cartilage defects, the cartilage decellularized extracellular matrix (CdECM) has attracted extensive interest. , CdECM cross-links can occur through self-assembly of internal proteins, or by grafting photo-cross-linkable moieties, e.g., methacrylic anhydride to enable photo-cross-linking, or by combining CdECM with routinely used polymers like silk fibroin or alginate for enhanced physical polymerization or Ca 2+ -mediated cross-linking . However, few studies have explored the adhesion between the hydrogel and native cartilage, which is essential for cartilage repair in a load-bearing environment to avoid hydrogel displacement.…”
Section: Introductionmentioning
confidence: 99%